Madras Third Five-Year Plan - Planning Commission (Planning Commission)
State Seed Farms. Carried over from Second Plan. Location Throughout the State in suitable lands. Scope and main components items (describe fully). The scheme is intended to multiply rapidly primary seeds of improved strains in State Seed Farms to be established all over the State and to make each tract self sufficient in the supply of quality seeds of all principal crops grown therein.
Madras State